A Silent Alarm at Occupational Evaluation Two Months after a Normal Painful ECG: A Case of Wellens’ syndrome - Giuseppe Di Stolfo; Sandra Mastroianno; Giovanni De Luca; Domenico Rosario Potenza; Nicola Marchese; Carlo Vigna; Raffaele Fanelli (Case Reports in Cardiology)
We describe a case of a 42-year-old man, with a previous episode of angina and a normal ECG and serum cardiac markers, and a two months later finding of biphasic T wave in leads V2-V3 and deeply inverted T wave in V4-V5 at a asymptomatic occupational evaluation. This is a typical ECG pattern of Wellens’ syndrome. A subsequent coronary angiography showed a critical stenosis of proximal left anterior descendent. We underline the careful value of prolonged observation in chest pain unit and repetitive ECG evaluation also during pain-free period after an angina episode, to exclude an earlier T wave pseudonormalization.